Distribusi Kandungan Kimia Kayu Kelapa (Cocos nucifera L) Distribution of Chemical Compounds of Coconut Wood (Cocos nucifera L) - Isna Yuniar Wardhani; Surjono Surjokusumo; Yusuf Sudo Hadi; Naresworo Nugroho (Masyarakat Peneliti Kayu Indonesia, 2004)
Within a tree from base to top (longitudinal) and dermal to core (lateral), the chemical compounds of wood such us celluloses, lignin, holocelluloses, ash content and extractives are different. The distribution should be known to process the wood, including coconut wood, easily and to utilize the wood optimally. The objective of this study was to determine the distribution of chemical compound of coconut wood within a tree. The analysis was conducted according to TAPPI Standard with three replications for each sample. Average values and graphs were use to analyze the results.The results indicated that coconut wood contains of wood extractives that soluble in hot water of 3.75 8.92%; alcohol benzene of1.88 8.78%; 1% NaOH of 18.76 33.61%; ash content of 0.75 4.08%; celluloses of 28.1 36.55%; holocelluloses of 69.51 80.07% and lignin of 26.58 36.35%. From base to top, wood extractives soluble in 1% NaOH increased but in other solutions did not have uniform distributions. Laterally, only holocelluloses and lignin did not have uniform distributions, whereas the others increased from dermal to core